FUNGSI DINAS SOSIAL DALAM PEMBERDAYAAN EKS WANITA TUNA SUSILA DI KOTA PEKANBARU - Suhaidah Lili Wandari; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Economic empowerment of ex-prostitutes is an assistance provided by the Pekanbaru city Social Service for ex-prostitutes. This is very important to supply the basic needs of every citizen which includes social rehabilitation, assurance, social empowerment and social protection. This research was conducted at the Social Service of Pekanbaru city. The formulation of the problem in this research was how the function of the Pekanbaru city Social Service in the economic empowerment of ex-prostituted in Pekanbaru city and what factors affected the function of the Social Service in the economic empowerment of ex-prostitutes in Pekanbaru city. The purpose of this researchare to know the function of the Pekanbaru city Social Service in the economic empowerment of ex-prostituted inPekanbarucity and what factors influenced the function of the Social Service in the economic empowerment of ex-prostitutes in Pekanbaru city. This research use the concept of organizational theory by Wursanto (2005: 270). This research uses qualitative research methods with descriptive data assessment and data analysis techniques using interactive models from Milles and Huberman cited by Sugiyono (2008: 142). The type and source of this data are primary data and secondary data, while the data collection technique of the research uses interview, observation and documentation techniques. The results of this research can be identified based on the following indicators (1) planning activities, the Pekanbaru city Social Service makes training activities for ex-prostituted women (2) Organizing, in carrying out this program the Pekanbaru city Social Service collaborates with Utama Riau Foundation (3) giving motivation (motivating), ex-prostitute women get motivation in the form of direction from the Utama Riau Foundation appointed by the Social Service as the executor of Productive Economic Business (4) controlling, every month the Utama Riau Foundation monitors the program of Productive Economic Business run by women who are prostitutes. Keywords : Economic Empowerment, Organization, Ex-Prostitutes